EDUKASI MICROSOFT OFFICE WORD BAGI SANTRI KMI DI PONDOK MODERN AL-MUJAHIDUL AMIN - Khair, Muhammad Saiful; Faridatunnisa, Nor; Munir, Muhammad Wildanul (LPPM Institut Pendidikan Nusantara Global, 2024)
The ability to operate office applications, one of which is Microsoft Office Word, is nowadays very important. This is because the development of science is very rapidly growing, thus forcing humans to always innovate to find more effective and efficient ways of working. However, the demand to master knowledge related to the Microsoft Office Word application is not owned by KMI students at Pondok Modern Al-Mujahidul Amin. This encourages the author to conduct Microsoft Office Word application training to improve the knowledge of its human resources. This training uses the training method, which is divided into the planning stage, preparation stage, implementation stage and training stage. The results showed that the knowledge of KMI students after the training became better. In addition, there are other by-products, namely learning modules that are useful to support the learning process of KMI students at Pondok Modern Al-Mujahidul Amin. These results are important to know so that future researchers can develop the research that has been done.